Differentiation of Traditional Frozen Food of Uli Ketan by Addition of Kidney Beans and Oyster Mushroom Filling - Suryani, Dede Irma; Priatini, Woro (Gastronomy Tourism Journal, 2020)
This research aims to make a variant of Uli Ketan- Indonesian traditional sticky rice. Fried Uli ketan becomes one of Indonesian famous traditional foods especially in West Java known as â€œUlenâ€. Commonly, Sundanese people made Uli from some ingredients such as glutinous rice, coconut, and water. However, in this study, the authors tried to remake the ingredients by adding red kidney beans and oyster mushroom as its filling. Based on a survey, Uli ketan is still familiar among community although 66,8% of the respondents said that they were bored with the taste and display of traditional Uli. If this condition is not taken into account, probably Uli Ketan will not sustain within the community. Thus, modification is needed to develop its flavor and shape in order to make the food more interesting. As result of a survey conducted by the authors show that 97,1% of respondents agreed that Uli Ketan should be more varied in terms of flavor and shape. Based on primary data, the authors combined the taste of traditional Uli Ketan with a new taste and made it into a fresh shape which are more desired by consumers. Nevertheless, the author maintained the same nutrient value of fiber and protein in the product and authenticity in the making process. This research applied experimental method by finding the best recipe formula through using testing product quality according to Marsum (2005). At the last, to keep the product storage longer, it was packaged by using freezing method.